Empowering Biosemiotics - Lassiter, Charles (Rivista Italiana di Filosofia del Linguaggio, 2022)
One way to understand the basic semiotic relation is that a sign-vehicle signifies an object to an interpretant. Biosemioticians sometimes talk about this relationship in terms of “codes”. When thinking about this relationship in the context of language, a natural move is to conceptualize semiotic relationships among speakers, meanings, and utterances as codes: speakers encode messages in sentences, which are then decoded by an interpreter. This view of communication is inconsistent with core tenets of a distributed approach to language, which holds that language is an embodied and encultured activity taking place across multiple timescales. I argue that a neo-Aristotelian metaphysics can be of help. A sign’s pointing to an object for an interpreter is a triadic relation, which can be described in terms of “abilities” or “powers”. On this view, talk about “codes” is eliminated in favor of talk about powers of agents and utterances.